Radiotherapy plus hyperthermia shows effectiveness in painful bony metastases—indicated only for selected patients with extended live expectancy and radiotherapy resistant tumor! - van Rhoon, Gerard Cornelis; van Holthe, Jeannette Maria Leonora (Therapeutic Radiology and Oncology, 2018)
Solid tumors are known to frequently metastasize to the bony structures with incidence varying strongly by tumor type and stage (1). Having bone metastasis is associated with a poor prognosis and a survival expectancy of several months. Bone metastases have a large impact on the quality of life as they cause severe and debilitating effects, like pain, spinal cord compression, hypercalcemia, pathologic fractures and neurologic deficits (1-3). Radiotherapy has an important role in the treatment of bone metastases. It is recognized for its low incidence of side effects and considered time efficient.